Precoding for secrecy rate maximisation in cognitive MIMO wiretap channels. Issue 21 (1st October 2015) - Fang, Bing; Qian, Zuping; Zhong, Wei; Shao, Wei
Abstract : The problem of physical layer security in a cognitive MIMO wiretap channel is studied. The problem is formulated as a secrecy rate maximisation (SRM) problem, and solved by a successive convex approximation (SCA) method. With the SCA method, the non‐convex part of the SRM problem is approximated by its first‐order Taylor expansion. Then, relying on solving a series of convexified optimisation problems, an iterative precoding algorithm is developed.